Come together now: Dynamic body-formation of key regulators integrates environmental cues in plant development - Burkart, Rebecca C.; Eljebbawi, Ali; Stahl, Yvonne (Frontiers in Plant Science, 2022)
Plants as sessile organisms are constantly exposed to changing environmental conditions, challenging their growth and development. Indeed, not only above-ground organs but also the underground root system must adapt accordingly. Consequently, plants respond to these constraints at a gene-regulatory level to ensure their survival and well-being through key transcriptional regulators involved in different developmental processes. Recently, intrinsically disordered domains within these regulators are emerging as central nodes necessary not only for interactions with other factors but also for their partitioning into biomolecular condensates, so-called bodies, possibly driven by phase separation. Here, we summarize the current knowledge about body-forming transcriptional regulators important for plant development and highlight their functions in a possible environmental context. In this perspective article, we discuss potential mechanisms for the formation of membrane-less bodies as an efficient and dynamic program needed for the adaptation to external cues with a particular focus on the Arabidopsis root. Hereby, we aim to provide a perspective for future research on transcriptional regulators to investigate body formation as an expeditious mechanism of plant-environment interactions.